Fiber Optic Sensors and Fiber Lasers - Jeon, Min Yong (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The optical fiber industry is emerging from the market for selling simple accessories using optical fiber to the new optical-IT convergence sensor market combined with high value-added smart industries such as the bio industry. Among them, fiber optic sensors and fiber lasers are growing faster and more accurately by utilizing fiber optics in various fields such as shipbuilding, construction, energy, military, railway, security, and medical.This Special Issue aims to present novel and innovative applications of sensors and devices based on fiber optic sensors and fiber lasers, and covers a wide range of applications of optical sensors. In this Special Issue, original research articles, as well as reviews, have been published.